Pengaruh Ekstrak Daun Kelor sebagai Priming Organik terhadap Perkecambahan Biji Kopi Arabika - Sari, Fanny Septiani; Triani, Nova; Djarwatiningsih, Djarwatiningsih (BIOEDUSCIENCE, 2025)
Background: Hard Arabica coffee seeds cause slow germination, but this can be accelerated by increasing their viability through seed priming techniques. The objective of this study was to determine the effect of concentration and duration of immersion in an organic priming solution extracted from moringa leaves on germination results and to identify the appropriate concentration and duration of immersion. Methods: This study was conducted from October to December 2024 at the Greenhouse in Sidorejo Village, Krian District, Sidoarjo, and the Production Laboratory of the Faculty of Agriculture, Universitas Pembangunan Nasional “Veteran” Jawa Timur. The study involved two treatment factors applied to Arabica coffee seeds: the concentration of the organic priming solution made from moringa leaf extract and the soaking duration. Results: The combination of treatment factors—concentration of moringa leaf extract solution and soaking duration—showed a significantly higher number of normal seedlings compared to abnormal seedlings, dead seeds, hard seeds, and fresh seeds. Conclusions: The optimal concentration of moringa leaf extract solution is 12%, and the optimal soaking duration is 38 hours